Interval Oscillation Criteria of Second-Order Nonlinear Dynamic Equations on Time Scales - Yang-Cong Qiu; Qi-Ru Wang (Discrete Dynamics in Nature and Society)
Using functions in some function classes and a generalized Riccati technique, we establish interval oscillation criteria for second-order nonlinear dynamic equations on time scales of the form (p(t)ψ(x(t))xΔ(t))Δ+f(t,x(σ(t)))=0. The obtained interval oscillation criteria can be applied to equations with a forcing term. An example is included to show the significance of the results.